Effect of ACL graft material on joint forces during a simulated in vivo motion in the porcine knee: Examining force during the initial cycles. Issue 11 (6th August 2014) - Boguszewski, Daniel V.; Wagner, Christopher T.; Butler, David L.; Shearn, Jason T.
ABSTRACT This study compared three‐dimensional forces in knees containing anterior cruciate ligament (ACL) graft materials versus the native porcine ACL. A six‐degree‐of‐freedom (DOF) robot simulated gait while recording the joint forces and moments. Knees were subjected to 10 cycles of simulated gait in intact, ACL‐deficient, and ACL‐reconstructed knee states to examine time zero biomechanical performance. Reconstruction was performed using bone‐patellar tendon‐bone allograft (BPTB), reconstructive porcine tissue matrix (RTM), and an RTM‐polymer hybrid (Hybrid). Forces and moments were examined about anatomic DOFs throughout the gait cycle and at three key points during gait: heel strike (HS), mid stance (MS), toe off (TO). Compared to native ACL, each graft restored antero‐posterior (A‐P) forces throughout gait. However, all failed to mimic normal joint forces in other DOFs. For example, each reconstructed knee showed greater compressive forces at HS and TO compared to the native ACL knee. Overall, the Hybrid graft restored more of the native ACL forces following reconstruction than did BPTB, while RTM grafts were the least successful. If early onset osteoarthritis is in part caused by altered knee kinematics, then understanding how reconstruction materials restore critical force generation during gait is an essential step in improving a patient's long‐term prognosis. © 2014 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:1458–1463, 2014.